The Concept of Values in Florian Znaniecki’s Early Work - Kaczmarczyk, Michał Roch (Stan Rzeczy, 2018)
One of the central concepts of The Polish Peasant in Europe and America, especially highlighted in the “Methodological Note,” is the relationship between values and attitudes which frames the subsequent empirical analyses and conclusions. The aim of the present article is to reconstruct Florian Znaniecki’s early idea of values in order to demonstrate its originality and later influence on his sociological contributions. As the author argues, Znaniecki’s early insights with regard to values allow us to reconsider his collaboration with William Thomas and to interpret The Polish Peasant as a part of Znaniecki’s long-term research programme.